Measurement and Analysis of the Extreme Physical Shock Environment Experienced by Crane-Mounted Radiation Detection Systems - Matthew Boyd; Jennifer Erchinger; Craig M Marianno; Gene Kallenbach (International Journal of Nuclear Security, 2019)
At ports of entry, radiation detectors could be mounted on container gantry crane spreaders to monitor cargo containers entering and leaving the country. These detectors would have to withstand the extreme physical conditions experienced by these spreaders during normal operations. Physical shock data from the gable ends of a spreader were recorded during the loading and unloading of a cargo ship by two hard mounted PCB Piezotronics model 340A50 accelerometers and two Lansmont SAVER 9X30 units (with padding). The majority of large shocks were observed in the vertical direction. The Lansmont units recorded mean shocks of 22.215 ± 1.174 and 23.776 ± 1.140 g, while the PCB accelerometers recorded mean shocks of 31.608 ± 1.798 and 37.072 ± 2.015 g in this direction. Maximum shocks were as high as 118.854 g. A scatter plot of observed peak acceleration versus velocity change is presented to allow comparison with the damage boundary curve for any planned instrumentation for future systems. It is hoped that the results of this research will aid in the design of future crane-mounted systems.
Keywords: Radiation detection; Border Security; Spreader-Bar crane